Paediatric Palliative Care - Monterosso, Leanne; De Graves, S. (Ausmed Publications, 2003)
Paediatric palliative care can be an emotive clinical issue. Although some issues in palliative care are similar in adults and children, there are several striking differences. These differences pose distinctive challenges to nurses who care for children with life-threatening conditions and their families. This chapter provides an overview of the issues involved in paediatric palliative care, and the strategies that can be used in a comprehensive approach to care.